Acoustics of hoarseness - R, Vaidyanathan; RK, Oza (Journal of All India Institute of Speech and Hearing)
Hoarseness is a symptom of laryngeal pathology. An acoustic analysis of the voice may provide the first accurate information about the pathologic changes in the larynx or voice disorders. The word ’hoarseness’ includes several kinds of vocal abnormality. It is assumed that normal voice results from normal vibration of the vocal folds and hoarseness is the result of some sort of abnormal vibrations. Normal phonation requires complete approximation, adequate tension and regular vibrations. If any of these requisites are disturbed for any reason, resultant condition could be hoarseness. Approximation, tension and vibrations could be disturbed by growth in the vocal folds, by paralysis, by thickening of the cords etc. In hoarseness the production of voice is disturbed because the vibratory behaviour of the cords are altered. The vibratory irregularities will be reflected in the acoustic analyses of such voice